Enhancing catalytic activity of Fe3O4 for electrochemical water oxidation via the coupling of OER-inert Au. (29th June 2022) - Zhang, Wenyan; Guan, Hangmin; Hu, Yingfei; Wang, Wei; Yang, Xiaoli; Kuang, Caiyuan
Abstract: Interfacial charge transfer efficiency and electronic states of active sites are two essential issues to restrict catalytic activity of electrocatalysts for oxygen evolution reaction (OER). In this work, we show that although Au is recognized to be inert towards OER, the catalytic activity of Fe3 O4 catalyst for OER was highly boosted by coupling Fe3 O4 with Au to address these two issues. Here, Au nanoparticles were attached to hierarchical Fe3 O4 microsphere through electrochemical deposition, a mild and rapid approach that can be accomplished within 3 min and requires no sophisticated equipment. With the coupling of Au, interfacial charge transfer resistance of Fe3 O4 declined remarkably. On the other hand, oxidability of Fe sites and electron accepting capability of Au sites was elevated due to strong interaction between Au and Fe3 O4 . Owing to these two merits induced by Au, Fe3 O4 exhibited enhanced catalytic activity for OER. The potential of Fe3 O4 to obtain 10 mA/cm 2 decreased by 640 mV, the current density was amplified up to 2.5 fold at the potential of 2 V (vs SCE), and the Tafel slop was reduced by 146 mV/dec. Graphical abstract: This work shows that the catalytic activity of an earth-abundant electrocatalyst (Fe3 O4 ) for OER reaction was boosted by coupling it with OER-inert Au. It is found that the coupling of Au not only facilitated charge transfer efficiency of the catalyst, but elevated the oxidability of Fe sites and electron accepting capability of Au sites. Thereby, when coupled with Au, Fe3 O4 exhibited enhanced current density, reduced overpotential, and smaller Tafel slop. Image 1 Highlights: Enhance catalytic activity of Fe3 O4 for OER reaction via coupling of OER-inert Au. Effectively promoted interfacial charge transfer with the decoration of Au. Modify the state of Fe sites and Au sites by strong interaction of Au with Fe3 O4 . An easy-to-handle and rapid way to couple Au with hierarchical Fe3 O4 microspheres.